The effects of intravenous dexmedetomidine premedication on intraocular pressure and pressor response to laryngoscopy and intubation - Alka Chandra; Reena Ranjan; Jay Kumar; Ashima Vohra; Vijay Kumar Thakur (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: Penetrating eye injuries are a challenge for the anesthesiologists in emergency due to increase in intraocular pressure (IOP). The aim of this study was to evaluate the effects of intravenous dexmedetomidine premedication on changes in IOP and hemodynamic response following laryngoscopy and tracheal intubation. Material and Methods: Hundred patients aged 18-60 years undergoing elective nonophthalmic surgery were divided into two groups of 50 each. Group D received a bolus dose of dexmedetomidine (0.4 μg/kg) diluted to 20 ml normal saline and Group C received normal saline (0.4 ml/kg) over 10 min as premedication. Heart rate (HR), systolic blood pressure (SBP) and IOP were measured and recorded before premedication (T1), 5 and 10 m after premedication (T2, T3), immediately after induction, intubation and then 1, 3, 5 min after intubation (T4, 5, 6, 7, 8). Results: HR was comparable in both groups at preoperative level, but it was significantly low in the drug group when compared with the control group at T4-T8 (P = 0.034, P < 0.001, 0.001, 0.036 and 0.001, respectively). The SBP was comparable in both the groups at baseline and till before induction. At T4-T8 there was a fall in SBP in Group D compared to the Group C (P = 0.045, P = 0.007, 0.001, 0.001 and 0.001, respectively). The baseline IOP was comparable in both the groups (P = NS). There was a significant fall in the IOP in Group D, 5 min after the drug infusion compared to Group C, which was sustained till 5 min after intubation (T8) (P < 0.001 at all intervals). Conclusion: Dexmedetomidine premedication in the dose of 0.4 μg/kg lowers the IOP and attenuates the pressor response to laryngoscopy and intubation.